2015
DOI: 10.1111/bju.12983
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of various treatment procedures for lower pole renal calculi: a systematic review and network meta‐analysis

Abstract: Objective To compare the effectiveness of various treatments used for lower pole renal calculi. Methods We searched PubMed, EMBASE, CINAHL, the Cochrane Collaboration's Database of Systematic Reviews, the Cochrane Collaboration Central Register of Controlled Clinical Trials as well as ClinicalTrials.gov for reports up to 1 April 2014. The search was supplemented with abstract reports from various urology conferences. All randomised, ‘blinded’ clinical studies including patients treated for lower pole renal cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
(109 reference statements)
1
12
0
Order By: Relevance
“…17 Despite its slight invasiveness, of all the treatment options, PCNL delivers the stone free rate more than 90% for lower pole stones >20mm. [18][19][20][21] In the present study, the overall stone free rate for PCNL in six weeks was 92.6% for stone size less than 20mm and 90.7% for stone size >20mm which was comparable to the stone free rate in the series by Netto et al and Cass AS. 22,23 The study also showed that the stone free rate in relation to stone size was not statistically significant ( P value o.78).…”
Section: Discussionsupporting
confidence: 83%
“…17 Despite its slight invasiveness, of all the treatment options, PCNL delivers the stone free rate more than 90% for lower pole stones >20mm. [18][19][20][21] In the present study, the overall stone free rate for PCNL in six weeks was 92.6% for stone size less than 20mm and 90.7% for stone size >20mm which was comparable to the stone free rate in the series by Netto et al and Cass AS. 22,23 The study also showed that the stone free rate in relation to stone size was not statistically significant ( P value o.78).…”
Section: Discussionsupporting
confidence: 83%
“…The treatment of lower pole renal calculi is a difficult point in urology. As the anatomical structure of the lower calyceal is not conducive for stone excretion, ESWL is less effective in the treatment of LPSs [1,16,17]. Some surgeons believed that either RIRS or PCNL surgery is needed even if the diameter of LPSs is less than 1.0 cm [18].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of lower pole renal calculi is a difficult point in urology. As the anatomical structure of the lower calyceal is not conducive for stone excretion, ESWL is less effective in the treatment of LPSs [1, 16,17]. Some surgeons believed that either RIRS or PCNL surgery is needed even if the diameter of LPSs is less than 1.0 cm [18].…”
Section: Discussionmentioning
confidence: 99%